Prevention of hate speech targeting groups in Finland and Japan : A comparative analysis between criminal and non-criminal approaches - Lyra, Maisa (My University, 2025)
This thesis compares Finland and Japan’s diverging approaches to preventing hate speech targeting a population group. The objective of the thesis is to find and explain similarities and differences in the preventive measures, as well as observe any room for improvement. Utilizing comparative legal research, the thesis explores how hate speech as a complex socio-legal phenomenon has been addressed in the countries. The methodological framework combines functionalism and the law-in-context method. The social and political context are examined to bring forth the underlying reasonings for the different approaches. The thesis also analyses the significance of freedom of speech as a constraint to prohibiting hate speech. The central question is whether a group can be recognized as a target of hate speech, and if one can be held accountable and punished for engaging in hate speech targeting a group. Both criminal and noncriminal national legal solutions are analyzed on the level of law and in practice. The source material covers national legislation, international conventions, reports by international bodies and scholarly articles. The thesis finds that a group can be legally considered a victim of hate speech in both countries, but only the Finnish regulation constitutes a direct criminal liability for the act. Case law suggests that punishment for hate speech is also possible in Japan, although the legal praxis is not as established. Finland has issues in protecting individuals from hate speech, and growing hate crime rates, whereas the scope of the Japanese hate speech law protects only some selected minorities and should be extended to cover more vulnerable minorities.

Tämä tutkielma vertailee Suomen ja Japanin keskenään eriäviä lähestymistapoja kansanryhmiin kohdistuvan vihapuheen torjumiseksi. Tutkielman tavoite on löytää ja selittää samankaltaisuuksia ja eroavaisuuksia lähestymistavoissa, sekä havaita kehityskohteita. Tutkielma tarkastelee vertailevan oikeustieteen keinoin, miten vihapuheseen monitahoisena sosiooikeudellisena ilmiönä on reagoitu maissa. Metodologinen viitekehys yhdistelee funktionalismia sekä law-in-context metodia. Taustalla olevia syitä lähestymistapojen eroille etsitään yhteiskunnallista ja poliittista kontekstia tarkastelemalla. Tutkielma analysoi myös sananvapauden merkitystä rajoitteena vihapuheen kieltämiselle. Keskeinen kysymys on, tunnistetaanko ryhmä vihapuheen uhriksi, ja voiko ryhmään kohdistetusta vihapuheesta joutua rangaistusvastuuseen. Niin rikosoikeudellisia kuin muita kansallisen oikeuden ratkaisuita analysoidaan kirjoitetun lain ja käytännön tasolla. Lähdeaineisto koostuu kansallisista laeista, kansainvälisistä sopimuksista, kansainvälisten toimijoiden raporteista sekä akateemisista artikkeleista. Tutkimus osoittaa, että ryhmän voi lain nojalla katsoa vihapuheen kohteeksi, joskin vain Suomessa säätely perustaa rikosoikeudellisen vastuun. Ennakkotapausten perusteella rangaistusvastuu on mahdollinen myös Japanissa, mutta käytäntö ei ole aivan yhtä vakiintunut. Haasteita Suomessa tuottavat yksilön puutteellinen suoja vihapuheelta sekä lisääntyvä viharikollisuus, kun taas Japanin vihapuhelaki suojaa ryhmiä hyvin valikoiden, ja sitä tulisi laajentaa kattamaan useampia vähemmistöryhmiä.
Keywords: Hate speech, Criminalisation, Freedom of expression, Legal comparison, Functionalism, Finnish law, Japanese law, Minority group protection, Vihapuhe, Kriminalisointi, Sananvapaus, Oikeusvertailu, Funktionalismi, Suomen laki, Japanin laki, Vähemmistöryhmien suojelu